Water-soluble polyvinyl alcohol film and preparation method thereof
By combining PVA resins and auxiliary agents with different molecular weights and alcoholylation, the problem of yellowing and poor fluidity of polyvinyl alcohol water-soluble films in hot processing is solved, and a film with high water-soluble temperature and good mechanical properties is prepared. , suitable for a variety of applications.
Patent Information
- Application Number
- CN202411543603.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyvinyl alcohol water-soluble films are prone to yellowing during thermal processing, and PVA resins with high single alcohol lysis have poor fluidity, and the melting temperature is similar to the decomposition temperature, resulting in uneven surface of the film and degradation of water-soluble properties and mechanical properties.
Through the blending of PVA resins with different molecular weights and alcoholylation, combined with auxiliary agents such as talc, starch, calcium stearate, etc., step-by-step plasticization method and the method of controlling the temperature and duration of the mixture are used to destroy the internal and external hydrogen of PVA molecules. Bonds, reduce melting point, improve rheology, avoid carbonization and decomposition, and prepare water-soluble polyvinyl alcohol films.
A polyvinyl alcohol film with a water-soluble temperature greater than 45°C has good tensile strength and biodegradability, avoiding film yellowing and plasticizer precipitation, and improving thermal processing stability and production efficiency.
Smart Images

Figure BDA0005113297370000051 
Figure BDA0005113297370000151 
Figure BDA0005113297370000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyvinyl alcohol films, and in particular relates to a water-soluble polyvinyl alcohol film and a preparation method thereof. Background Art
[0002] Polyvinyl alcohol (PVA) is a synthetic water-soluble high molecular polymer. In recent years, due to its good water solubility, non-toxicity and biodegradability, PVA fully meets the national green environmental protection and sustainable development strategic requirements and has good development prospects. A variety of high value-added water-soluble film products based on polyvinyl alcohol have been widely used in the market. According to different specific applications, they can be divided into cold water soluble, warm water soluble and hot water soluble PVA film products.
[0003] PVA thermal processing includes manufacturing processes such as solution casting, melt extrusion, melt extrusion blow molding, and continuous biaxial orientation. Among them, the solution casting method produces PVA water-soluble films with high uniformity, but its processing cost is high and its production capacity is low; the traditional blow molding film forming method is a processing method with low energy consumption and high production capacity, but its application range is limited by the physical and chemical properties caused by the PVA structure. The physical and chemical properties of PVA are mainly determined by its degree of polymerization and alcoholysis. Its solubility in water is mainly determined by the degree of alcoholysis. During alcoholysis, the hydrophobic vinyl acetate group in the PVA molecule is gradually replaced by the hydrophilic hydroxyl group. As the degree of alcoholysis increases, the number of hydrophilic hydroxyl groups increases, and a large number of strong intramolecular hydrogen bonds are formed between the hydroxyl groups, making it more difficult for water molecules to enter the crystalline part. Therefore, common water-soluble PVA films choose to use PVA raw materials with a higher degree of alcoholysis, which are insoluble in cold water but soluble in warm water. However, when a single PVA resin with a high alcoholysis degree is heat-processed, the PVA resin has poor fluidity, the melting temperature is close to the decomposition temperature, and a large amount of decomposition and carbonization is prone to occur during melting, resulting in uneven film surface, decreased water solubility and mechanical properties, and plasticizer precipitation in high humidity environments. In addition to using plasticizers to broaden the PVA melt heat processing window, common PVA heat processing modification methods also include adding starch, calcium stearate and other processing aids to improve the heat processing stability of polyvinyl alcohol and the opening of blown film. However, since starch has multiple hydroxyl groups on the glucose unit, direct heating of starch under normal conditions will decompose and carbonize, and the prepared film will also have the problem of yellowing. Summary of the invention
[0004] The object of the present invention is to provide a water-soluble polyvinyl alcohol film and a preparation method thereof, so as to solve the problem that the PVA water-soluble film is prone to yellowing. The object of the present invention can be achieved by the following technical solutions:
[0005] A method for preparing a water-soluble polyvinyl alcohol film comprises the following steps:
[0006] The first step is to stir and mix the compound plasticizer and the PVA resin powder, and then let it stand to obtain a pre-processed PVA mixed resin raw material;
[0007] The second step is to stir and mix the pre-processed PVA mixed resin raw material and the auxiliary agent to obtain a melt-processable polyvinyl alcohol composition;
[0008] The third step is to obtain a water-soluble polyvinyl alcohol film by melt extrusion granulation and film blowing of the melt-processable polyvinyl alcohol composition.
[0009] Furthermore, the average degree of polymerization of the PVA resin powder is 1500-2400, and the average degree of alcoholysis is 86%-99%. In the present invention, the thermal processing performance of the PVA resin powder is improved by adopting a method of compounding and blending modification of PVA resins with different molecular weights and alcoholysis degrees. In the method of the present invention, PVAs with different molecular weights and alcoholysis degrees are physically blended. Since the water solubility and melt processing temperature of the PVA resin are closely related to the degree of polymerization and the degree of alcoholysis, the hydrogen bonding effect formed between different types of PVAs can destroy the strong hydrogen bonds of the single PVA itself, reduce the melting point of the blended PVA, and improve the thermoplastic processing performance of the PVA resin. At the same time, the mixed PVA resin raw material used in the method of the present invention avoids the influence of the single raw material thermal processing preparation film having a regular molecular arrangement, high crystallinity, and easy occurrence of plasticizer precipitation in a high humidity environment. The present invention realizes the control of the water-soluble temperature of the PVA film by compounding different grades of PVA to regulate the average degree of polymerization and alcoholysis of the PVA raw material, and the water-soluble temperature of the PVA water-soluble film prepared by the method of the present invention is greater than 45°C. And compared with common physical blending modification, it will not introduce other blending components and impurities, and will not reduce the purity of the product.
[0010] The preferred PVA resin powder formula adopted in the method of the present invention destroys the hydrogen bonds within and between PVA molecules. The weakening of the hydrogen bonds between PVA molecules and the reduction of entanglement between molecular chains lead to the improvement of the melt processing rheological properties of the PVA resin powder, thereby effectively reducing the energy consumption input in the actual production of PVA water-soluble films and improving production efficiency.
[0011] Furthermore, in parts by weight, the raw materials of the water-soluble polyvinyl alcohol film include 100 parts of PVA resin powder, 10-15 parts of compounding auxiliary agents, and 22-32 parts of compounding plasticizers.
[0012] Furthermore, the auxiliary agent is one of talc, starch, calcium stearate and magnesium stearate.
[0013] Furthermore, the compound plasticizer includes water and a small molecule plasticizer, and the small molecule plasticizer is a small molecule plasticizer containing hydroxyl groups and / or amine groups, and the small molecule plasticizer is selected from two or more of polyethylene glycol, ethylene glycol, diethylene glycol, triethylene glycol, diethanolamine, propylene glycol and triethanolamine. In the present invention, the regularity of the molecular structure of the prepared polyvinyl alcohol thermoplastic processing powder is destroyed by adjusting the type of plasticizer and the compound formula ratio. The hydroxyl and amine groups contained in the added hydroxyl and / or amine compound plasticizer can form hydrogen bonds with the hydroxyl groups of the PVA molecules, and can also form complexes with the PVA molecules, which can effectively destroy the internal structure of the PVA molecules, reduce the melting processing temperature of the PVA resin powder, and avoid the problem of carbonization and decomposition of raw materials during high-temperature melting during thermal processing.
[0014] Furthermore, the compound plasticizer is obtained by mixing water and a small molecule plasticizer containing hydroxyl groups and / or amine groups, and the mixing time is 15 minutes to 30 minutes.
[0015] Furthermore, in the first step, the stirring and mixing temperature is 25-60°C, the mixing time is 15min-3h, the stirring and mixing speed is 200-500r / min, and the standing time is 15min-30min;
[0016] In the second step, the mixing temperature is 25-60°C and the mixing time is 15min-5h;
[0017] In the third step, the polyvinyl alcohol composition can be melt processed for melt extrusion granulation: the feed rate is 15-40 r / min, the granulation temperature is 150-210°C, and the air cooling is performed to 20-40°C.
[0018] Furthermore, in the third step, melt extrusion granulation is performed under the condition of a vacuum degree of -0.04Mpa to -0.95Mpa. Water is a type of plasticizer in the hot melt processing of PVA, which affects the PVA melt extrusion fluidity, the mechanical properties of the PVA film, and the PVA thermal processing stability. Therefore, in the method of the present invention, the final water content of the PVA resin composition is controlled at 5% to 15% by controlling the mixing temperature and duration, and the vacuum degree is adjusted to -0.04Mpa to -0.95Mpa by using an exhaust fan device during the granulation process to remove steam from the powder melt during the granulation process, so as to achieve smooth preparation without foaming and avoid hollow PVA pellets caused by steam.
[0019] Furthermore, in the third step, melt granulation is performed to obtain melt-processable polyvinyl alcohol resin particles having a moisture content ranging from 0.3% to 2%.
[0020] Further, the prepared melt-processable polyvinyl alcohol resin particles are heated to a molten state with a melting temperature of 150°C to 220°C, extruded by a screw blow molding into a film, and wound up with a feeding speed of 20 to 30 r / min and a film thickness of 30 μm to 120 μm.
[0021] A water-soluble polyvinyl alcohol film is prepared by the above preparation method.
[0022] Beneficial effects of the present invention:
[0023] In the traditional one-step plasticizing method, PVA is plasticized after being blended with starch, and auxiliary agents such as starch will absorb most of the plasticizers, making PVA plasticized insufficient, and then causing PVA and auxiliary agents such as starch to be unable to be plasticized synchronously during hot processing. In the present invention, talcum powder, starch, calcium stearate and magnesium stearate are used as auxiliary agents with adsorption effects, and a step-by-step plasticizing method is adopted. After PVA is mixed with a plasticizer in advance, starch, talcum powder, calcium stearate and other powdered auxiliary agents are added through a step-by-step plasticizing process to improve the plasticizing effect of PVA, avoid the yellowing of the film caused by the excessively long hot processing time of PVA, and the starch, talcum powder and calcium stearate added in the inventive method are also conducive to improving the thermal stability of the PVA composition during hot processing, and improving the opening of the blown film.
[0024] The present invention overcomes the problem of raw material carbonization during the thermal processing of PVA by adjusting the proportion of PVA raw materials with different polymerization degrees and alcoholysis degrees for blending and modification, designs a compound plasticizer formula, and adds an auxiliary agent that can improve the thermal processing stability of polyvinyl alcohol resin powder, thereby achieving the preparation of a polyvinyl alcohol film with a water-soluble temperature greater than 45°C.
[0025] The water-soluble temperature of the PVA water-soluble film prepared by the present invention is greater than 45°C, and it has good tensile strength and biodegradability. The film product prepared after thermoplastic processing can be used as a tape substrate. The laundry bags, bed sheets and clothing packaging bags prepared by the high-quality PVA water-soluble film prepared by the present invention can achieve contactless cleaning to avoid the risk of contamination or infection. The PVA water-soluble film prepared by the present invention has good biodegradability and can be used as a drug film. As a carrier, it can be used to deliver drugs through various routes and exert local or systemic therapeutic effects, such as oral ulcer films, eye medicine films, hemostatic films, etc. In addition, the water-soluble polyvinyl alcohol film prepared by the present invention has good softness and tensile strength, so it can be used to print various patterns on curved surfaces. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a method for preparing a polyvinyl alcohol water-soluble film / resin raw material moisture content detection method comprising the following steps:
[0028] a. Set the temperature of the blast drying oven to 105℃, put the weighing bottle in to dry for 0.5h, take it out and place it in a desiccator to cool;
[0029] b. The mass of the weighing bottle is m0, and a sample of about 1g is added, so the weight of the sample and the bottle is m1;
[0030] d. Place the sample to be tested in a blast drying oven that has been kept at a constant temperature for 0.5h, and dry at 105℃ for 3h;
[0031] e. After drying, place the sample in a desiccator, cool it for 0.5h, then take it out and weigh its mass as m2;
[0032] f. For each sample, two groups of parallel samples are taken and the average value is taken. The moisture content is calculated as follows:
[0033]
[0034] The method for preparing a water-soluble polyvinyl alcohol film provided by the present invention comprises the following steps:
[0035] a. Add 1L pure water of corresponding temperature (25 / 45 / 60℃) into a 1L beaker and adjust the speed to 200r / min;
[0036] b. Balance the PVA water-soluble film in a constant temperature and humidity chamber for 24 hours, and measure the moisture content of the film after equilibrium;
[0037] c. Cut a film sample with a length and width of 8cm*8cm and a thickness of 40-80μm and fix it in a fixture. Immerse the sample in water and time it synchronously, and record the disintegration time and complete dissolution time (the disintegration and complete dissolution time occur when one corner of the water-soluble film falls off or the middle is damaged);
[0038] d. The samples were tested three times in parallel and the solubility of the water-soluble polyvinyl alcohol film was recorded.
[0039] The present invention provides a polyvinyl alcohol water-soluble film resin raw material melt index comprising the following steps:
[0040] a. Prepare polyvinyl alcohol sample powder according to the plasticizer formula and process;
[0041] b. Add 3-8g sample powder into the barrel, compact the sample to expel air, insert the piston into the barrel, preheat at a certain temperature (150-200℃) for 3 minutes, and add load;
[0042] c. Collect the pellets cut within a certain period of time, calculate their average mass, and calculate the melt index.
[0043] The tensile strength test of the polyvinyl alcohol water-soluble film provided by the present invention refers to GB / T1040.3-2006 Determination of tensile properties of plastics Part 3: Test methods for films and sheets.
[0044] The alcoholysis degree test of the polyvinyl alcohol composition provided by the present invention refers to GB / T12010.5-2010 Plastic polyvinyl alcohol material (PVAL) Part 5: Test method for determination of average degree of polymerization.
[0045] The polymerization degree test of the polyvinyl alcohol composition provided by the present invention refers to GB / T12010.2-2010 Plastic polyvinyl alcohol material (PVAL) Part 2: Test method for performance determination.
[0046] Example 1
[0047] By weight, 10 parts of glycerol solution, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0048] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0049] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0050] The melt temperature of the melt-processable polyvinyl alcohol composition was measured to be 196° C., the melt index was 27.65 g / 10 min, the water-soluble film and packaging material prepared by thermal processing had a thickness of 60±1 μm, and it completely dissolved in 93±2 s at 45° C.
[0051] Example 2
[0052] By weight, 15 parts of glycerol solution, 15 parts of polyethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 94% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0053] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of talc at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0054] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0055] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 195° C., and the melt index was 28.27 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm, and completely dissolved in 86±2 s at 45° C.
[0056] Example 3
[0057] By weight, 25 parts of glycerol solution, 5 parts of triethanolamine, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 2000 and an average degree of alcoholysis of 96% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0058] The obtained pre-processed PVA mixed resin raw material is mixed with 15 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0059] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0060] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 203° C., and the melt index was 26.45 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm, and completely dissolved in 53±2 s at 60° C.
[0061] Example 4
[0062] By weight, 20 parts of diethylene glycol, 10 parts of triethanolamine, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1900 and an average degree of alcoholysis of 88% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0063] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of calcium stearate at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0064] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0065] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 200° C., and the melt index was 27.12 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 40±2 s at 60° C.
[0066] Example 5
[0067] By weight, 20 parts of diethanolamine, 5 parts of polyethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1500 and an average degree of alcoholysis of 99% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0068] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0069] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0070] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 186° C., and the melt index was 29.03 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 77±2 s at 45° C.
[0071] Example 6
[0072] By weight, 10 parts of triethanolamine, 15 parts of triethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1600 and an average degree of alcoholysis of 97% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0073] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of magnesium stearate at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0074] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0075] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 193° C., and the melt index was 30.65 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 74±2 s at 45° C.
[0076] Example 7
[0077] By weight, 15 parts of ethylene glycol, 15 parts of triethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1800 and an average degree of alcoholysis of 90% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0078] The obtained pre-processed PVA mixed resin raw material is mixed with 15 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0079] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 190° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 190° C. and a feeding speed of 25 r / min.
[0080] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 194° C., and the melt index was 27.02 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm, and completely dissolved in 56±2 s at 45° C.
[0081] Comparative Example 1
[0082] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. The compound plasticizer was mixed with 100 parts of a single PVA resin powder with a degree of polymerization of 1700 and a degree of alcoholysis of 88% at 500 r / min at 45°C for 1 hour, and the pre-processed PVA mixed resin raw material was obtained after the mixing was allowed to stand for 15 minutes;
[0083] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0084] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 12 r / min and a granulation temperature of 210° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 210° C. and a feeding speed of 25 r / min.
[0085] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 209°C, and the melt index was 27.26 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 43±2 s at 25°C. The film was placed in an environment with a humidity of more than 90% for 24 hours, and plasticizer precipitated on the surface.
[0086] Comparative Example 2
[0087] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. The compound plasticizer was mixed with 100 parts of a single PVA resin powder with a degree of polymerization of 1700 and a degree of alcoholysis of 92% at 500 r / min at 45°C for 1 hour, and the pre-processed PVA mixed resin raw material was obtained after the mixing was allowed to stand for 15 minutes;
[0088] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0089] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 12 r / min and a granulation temperature of 210° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 210° C. and a feeding speed of 25 r / min.
[0090] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 210°C, and the melt index was 28.24 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 88±2 s at 45°C. The film was placed in an environment with a humidity of more than 90% for 24 hours, and plasticizer precipitated on the surface.
[0091] Comparative Example 3
[0092] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. The compound plasticizer was mixed with 100 parts of a single PVA resin powder with a degree of polymerization of 1700 and a degree of alcoholysis of 99% at 500 r / min at 45°C for 1 hour, and the pre-processed PVA mixed resin raw material was obtained after the mixing was allowed to stand for 15 minutes;
[0093] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0094] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 12 r / min and a granulation temperature of 210° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 210° C. and a feeding speed of 25 r / min.
[0095] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 217°C, and the melt index was 26.78 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 90±2 s at 45°C. The film was placed in an environment with a humidity of more than 90% for 24 hours, and plasticizer precipitated on the surface.
[0096] Comparative Example 4
[0097] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% and 10 parts of starch were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 500r / min at 45°C for 2h to obtain a melt-processable polyvinyl alcohol composition; the polyvinyl alcohol composition was melt-granulated under the conditions of a twin-screw granulator feeding speed of 15r / min and a granulation temperature of 200°C. The prepared water-soluble PVA particles were thermoplastically processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 200°C and a feeding speed of 25r / min.
[0098] The melt temperature of the melt-processable polyvinyl alcohol composition was measured to be 213° C., and the melt index was 15.46 g / 10 min. The pellets extruded by the heat processing were yellow in color, and the plasticizing effect of the prepared film was poor. It completely dissolved in 94±2 s at 45° C.
[0099] Comparative Example 5
[0100] By weight, 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% are mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. 25 parts of glycerol and 2 parts of water are mixed with the PVA mixed resin raw material at 500 r / min at 45°C for 1 hour, and the mixed raw material is allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0101] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0102] The polyvinyl alcohol composition was melt granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 210° C. The prepared water-soluble PVA particles were thermoplastic processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 210° C. and a feeding speed of 25 r / min.
[0103] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 217°C, and the melt index was 15.13 g / 10 min. The water-soluble film and packaging material prepared by the thermal processing had a thickness of 60±1 μm and completely dissolved in 115s±2s at 45°C. The film was placed in an environment with a humidity of more than 90% for 24 hours, and plasticizer precipitated on the surface.
[0104] Comparative Example 6
[0105] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 500r / min at 45°C for 2h to obtain a melt-processable polyvinyl alcohol composition; the polyvinyl alcohol composition was melt-granulated under the conditions of a twin-screw granulator feeding speed of 15r / min and a granulation temperature of 200°C. The prepared water-soluble PVA particles were thermoplastically processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 200°C and a feeding speed of 25r / min.
[0106] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 224°C, and the melt index was 24.69 g / 10 min. The thickness of the water-soluble film and packaging material prepared by the thermal processing was 60±1 μm. The inner and outer layers of the blown film were adhered and difficult to separate. The film was completely dissolved in 96s±2s at 45°C.
[0107] Comparative Example 7
[0108] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 2 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95%, a compound plasticizer, and 10 parts of starch were mixed at 500r / min at 45°C for 2 hours to obtain a melt-processable polyvinyl alcohol composition; the polyvinyl alcohol composition was melt-granulated under the conditions of a twin-screw granulator feeding speed of 15r / min and a granulation temperature of 200°C. The prepared water-soluble PVA particles were thermoplastically processed into water-soluble PVA film samples in a PVA film blowing machine at a film blowing temperature of 200°C and a feeding speed of 25r / min.
[0109] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 216°C, the melt index was 15.03 g / 10 min, the thickness of the water-soluble film and packaging material prepared by the thermal processing was 60±1 μm, and the film was completely dissolved in 98s±2s at 45°C.
[0110] Comparative Example 8
[0111] By weight, 10 parts of glycerol and 10 parts of ethylene glycol were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 60°C at 500r / min for 3 hours, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0112] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0113] The polyvinyl alcohol composition was melt-granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 200°C.
[0114] The melt temperature of the melt-processable polyvinyl alcohol composition was measured to be 215° C., the moisture content of the powder was 4.33%, and the melt index was 7.12 g / 10 min. The pellets prepared by the heat treatment were yellow, and the moisture content of the pellets was 0.02%, and film blowing was not possible.
[0115] Comparative Example 9
[0116] By weight, 10 parts of glycerol, 10 parts of ethylene glycol, and 7 parts of water were stirred and mixed at 50°C for 15 minutes to obtain a compound plasticizer. A total of 100 parts of PVA resin powder with an average degree of polymerization of 1700 and an average degree of alcoholysis of 95% were mixed at 30°C for 30 minutes to obtain a PVA mixed resin raw material. The compound plasticizer and the PVA mixed resin raw material were mixed at 45°C at 500r / min for 1 hour, and the mixed raw material was allowed to stand for 15 minutes to obtain a pre-processed PVA mixed resin raw material;
[0117] The obtained pre-processed PVA mixed resin raw material is mixed with 10 parts of starch at 45° C. for 1 hour, and the stirring mixing rate is preferably 500 r / min to obtain a melt-processable polyvinyl alcohol composition;
[0118] The polyvinyl alcohol composition was melt-granulated in a twin-screw granulator at a feeding speed of 15 r / min and a granulation temperature of 200°C.
[0119] The melting temperature of the melt-processable polyvinyl alcohol composition was measured to be 207° C., the moisture content of the powder was 20.27%, the melt index was 26.67 g / 10 min, and foaming occurred during granulation, so granulation could not be successfully performed.
[0120] The raw materials and amounts used in Examples 1 to 6 and Comparative Examples 1 to 9 are shown in Table 1 below:
[0121] Table 1
[0122]
[0123]
[0124] Compared with Example 1, Comparative Example 1 uses a single PVA resin powder with a polymerization degree of 1700 and an alcoholysis degree of 88%;
[0125] Compared with Example 1, in Comparative Example 2, a single PVA resin powder with a polymerization degree of 1700 and an alcoholysis degree of 92% was selected;
[0126] Compared with Example 1, in Comparative Example 3, a single PVA resin powder with a polymerization degree of 1700 and an alcoholysis degree of 99% was selected;
[0127] Compared with Example 1, in Comparative Example 4, PVA and starch were pre-mixed and then mixed with the compound plasticizer for plasticization;
[0128] Compared with Example 1, ethylene glycol and starch were not added in Comparative Example 5;
[0129] Compared with Example 1, no starch was added in Comparative Example 6;
[0130] Compared with Example 1, in Comparative Example 7, starch-compounded plasticizer-PVA resin is mixed and plasticized in one step;
[0131] Comparative Example 8: No water was added to the raw materials (the moisture content of the pellets was 0.02%);
[0132] In Comparative Example 9, the amount of water added to the raw materials is high (the moisture content of the pellets is 20.27%).
[0133] The water solubility (film thickness 60±1 μm) and melt index (200° C., 2.16 kg) of the polyvinyl alcohol water-soluble films prepared in Examples 1 to 6 and Comparative Examples 1 to 9 were recorded. The results are shown in Table 2 below:
[0134] Table 2
[0135]
[0136] The processing state comparison results of the polyvinyl alcohol water-soluble films prepared by Example 1 to Example 6 and Comparative Example 1 to Comparative Example 9 are shown in Table 3 below:
[0137] Table 3
[0138]
[0139] The melting temperatures of the polyvinyl alcohol water-soluble films prepared in Examples 1 to 6 and Comparative Examples 1 to 9 were recorded. The results are shown in Table 4 below:
[0140] Table 4
[0141]
[0142]
[0143] The tensile strength of the polyvinyl alcohol water-soluble films prepared in Examples 1 to 7 was recorded, and the results are shown in Table 5 below:
[0144] Table 5
[0145]
[0146] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0147] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a water-soluble polyvinyl alcohol film, characterized in that: The steps include: The first step is to stir and mix the compound plasticizer and the PVA resin powder, and then let it stand to obtain a pre-processed PVA mixed resin raw material; The second step is to stir and mix the pre-processed PVA mixed resin raw material and the auxiliary agent to obtain a melt-processable polyvinyl alcohol composition; The third step is to obtain a water-soluble polyvinyl alcohol film by melt extrusion granulation and film blowing of the melt-processable polyvinyl alcohol composition.
2. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: In parts by weight, the raw materials of the water-soluble polyvinyl alcohol film include 100 parts of PVA resin powder, 10-15 parts of compounding auxiliary agents, and 22-32 parts of compounding plasticizers.
3. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: The average polymerization degree of the PVA resin powder is 1500-2400, and the average alcoholysis degree is 86%-99%.
4. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: The auxiliary agent is one of talc, starch, calcium stearate and magnesium stearate.
5. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: The compound plasticizer comprises water and a small molecule plasticizer, and the small molecule plasticizer is a small molecule plasticizer containing a hydroxyl group and / or an amine group.
6. The method for preparing a water-soluble polyvinyl alcohol film according to claim 5, characterized in that: The small molecule plasticizer is selected from two or more of polyethylene glycol, ethylene glycol, diethylene glycol, triethylene glycol, diethanolamine, glycerol and triethanolamine.
7. The method for preparing a water-soluble polyvinyl alcohol film according to claim 5, characterized in that: The compound plasticizer is obtained by mixing water and a small molecule plasticizer, and the mixing time is 15 minutes to 30 minutes.
8. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: In the first step, the stirring and mixing temperature is 25-60°C, the mixing time is 15min-3h, the stirring and mixing speed is 200-500r / min, and the standing time is 15min-30min; In the second step, the mixing temperature is 25-60°C and the mixing time is 15min-5h; In the third step, the polyvinyl alcohol composition can be melt processed for melt extrusion granulation: the feed rate is 15-40 r / min, the granulation temperature is 150-210°C, and the air cooling is performed to 20-40°C.
9. The method for preparing a water-soluble polyvinyl alcohol film according to claim 8, characterized in that: In the third step, melt extrusion granulation is performed under a vacuum degree of -0.04Mpa to -0.95Mpa.
10. The method for preparing a water-soluble polyvinyl alcohol film according to claim 8, characterized in that: In the third step, melt granulation is performed to obtain melt-processable polyvinyl alcohol resin particles having a moisture content ranging from 0.3% to 2%.
11. The method for preparing a water-soluble polyvinyl alcohol film according to claim 1, characterized in that: The prepared melt-processable polyvinyl alcohol resin particles are heated to a molten state with a melting temperature of 150°C to 220°C, extruded by a screw and blown into a film, which is wound up with a feeding speed of 20 to 30 r / min and a film thickness of 30 μm to 120 μm.
12. A water-soluble polyvinyl alcohol film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 11.
Citation Information
Patent Citations
Fusion preparation method of polyvinyl alcohol film
CN101864132A
Water-resistant polyvinyl alcohol (PVA) film composition as well as fusion preparation method thereof
CN102234405A
Blow molded water-soluble polyvinyl alcohol thin film and preparation method and application thereof
CN109456555A
Biodegradable PVA instant film and preparation method thereof
CN109836739A
